A review article of UPLC and its emerging application and challenges and opportunities - G. Dharmamoorthy (Asian Journal of Pharmaceutics (AJP), 2025)
Ultra performance liquid chromatography (UPLC) has emerged as a powerful analytical tool in pharmaceutical applications, offering enhanced resolution, speed, and sensitivity compared to traditional high-performance liquid chromatography. This technique, which utilizes smaller particle sizes in the stationary phase and higher operating pressures, significantly improves the efficiency of drug analysis, quality control, and formulation development. UPLC plays a critical role in the separation and quantification of active pharmaceutical ingredients, excipients, and impurities in pharmaceutical products. It is widely employed in the analysis of complex matrices, such as biological fluids and dosage forms, enabling the accurate determination of drug concentration and pharmacokinetic parameters. In addition, UPLC is instrumental in the stability testing and shelf-life assessment of pharmaceuticals. The technique’s advantages, including reduced analysis time, lower solvent consumption, and high-throughput capabilities, make it a preferred choice in the pharmaceutical industry for both regulatory compliance and R and D purposes. This overview highlights the various pharmaceutical applications of UPLC, demonstrating its impact on drug development, quality assurance, and patient safety.